Technology, banking transactions and customer relationships in the banking industry - Bionat, Brenton; Magdato, Rose Anne; Olalia, Kristine; Pedroso, Nancy Grace; Tala-oc, Honey Zel
This study seeks to find out how the utilization of technology in banking transactions affects customer relationships.Specifically, it aims to identify the banking transactions that utilize technology, to describe how banking institutions promote customer relationships and to know how bank customers respond on the application of technology in banking transactions. The respondents of the study 30 bank customers in Iloilo City that were selected randomly and four bank employees. The bank customers, though aware of banking technologies, do not necessarily use them in making transactions except for ATMs. For the bank customers, technology when applied in services provided by the banks affects customer satisfaction but is not always a factor of customer retention. For the bank representatives, technology when applied in services provided by banks affects customer satisfaction and is often a factor of customer retention. It is recommended that banks should consider the following: (1) invest in more updated banking technologies, (2) invest on training for employees, (3) inform customers of others available modern technologies and how to use them and (4) improve the delivery of service. It is suggested that banks may lookk first at checking the effectiveness and efficiency of the technologies they used before looking at some investment decisions. It is suggested that banks look at technologies they used before looking at some investment decisions. It is suggested that banks look at investment decisions-investments in more updated banking technologies that can cope with the fast-changing standards of the customers when it comes to service. Efficiency will improve only when the banks take advantage of the capabilities of the technology. But before one may able to take advantage of the capabilities of the technology. But before one may be able to take advantage of the capabilities of the technology, one should know how to use them properly. Hence, it is suggested that banks invest on training for employees regarding how to use the technology which will not only increase the knowledge of bank employees on the application of technologies in banking but will also increase the confidence of bank employees on the services they are providing. It is also suggested that banks should inform their customers of other modern banking channels that may be used. Moreover, it is suggested that bank employees will not only undergo training on how to personally use modern technologies but will alo go through a series of seminars on how to effectively deal with customers and continuously satisfy them to retain them.